2014
DOI: 10.1001/jama.2014.1878
|View full text |Cite
|
Sign up to set email alerts
|

Risk of InvasiveHaemophilus influenzaeInfection During Pregnancy and Association With Adverse Fetal Outcomes

Abstract: IMPORTANCE UnencapsulatedHaemophilus influenzae frequently causes noninvasive upper respiratory tract infections in children but can also cause invasive disease, especially in older adults. A number of studies have reported an increased incidence in neonates and suggested that pregnant women may have an increased susceptibility to invasive unencapsulated H influenzae disease.OBJECTIVE To describe the epidemiology, clinical characteristics, and outcomes of invasive H influenzae disease in women of reproductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…Higher H. influenzae notification rates for infants, particularly neonates, the elderly, and women of childbearing age, were described before ( 30 , 31 ) and after ( 32 34 ) the introduction of routine Hib vaccination. In addition, several studies showed an increased burden of NTHi in groups more susceptible to infection, with high proportions of intensive care admission, high case-fatality rates, and frequent sequelae among survivors ( 2 , 29 , 32 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Higher H. influenzae notification rates for infants, particularly neonates, the elderly, and women of childbearing age, were described before ( 30 , 31 ) and after ( 32 34 ) the introduction of routine Hib vaccination. In addition, several studies showed an increased burden of NTHi in groups more susceptible to infection, with high proportions of intensive care admission, high case-fatality rates, and frequent sequelae among survivors ( 2 , 29 , 32 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Three cases were associated with second trimester fetal loss (Table ). Haemophilus influenzae is known to be associated with an increased risk of invasive infection during pregnancy, fetal loss and preterm birth …”
Section: Discussionmentioning
confidence: 99%
“…Population-based studies have proposed increased susceptibility to invasive H. influenzae infections during pregnancy. According to a surveillance data from England, pregnant women had 17-fold increased risk of invasive NTHi compared with non-pregnant women [7]. Among pregnant women with invasive H. influenzae, the incidence of pregnancy loss was 61%, 20% of which were lost prior to 25 weeks' gestation [7].…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence indicating a strong association between invasive NTHi infection during pregnancy and early pregnancy loss as well as invasive neonatal disease [6,7]. As the diagnosis relies on microbiological investigation of post-mortem placental and foetal samples, a significant proportion of NTHi-related pregnancy loss remains undiagnosed.…”
Section: Introductionmentioning
confidence: 99%